Preferensi Pendidik Atas Konsep Sekolah Ramah Anak di PAUD Inklusi - Falera, Ana (Kiddo: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Child-friendly schools in Early Childhood Education institutions are a concept that emphasizes an environment that supports children's overall development. Child-friendly schools in Early Childhood Education institutions tend to promote inclusivity, meaning they open the door for children with special or different needs to join the same learning environment as other children. This study on child-friendly schools in inclusive Early Childhood Education institutions was carried out using the literature study method. Data collection was carried out by collecting references relevant to the study theme in the form of previous research results and then drawing an analysis regarding child-friendly schools in inclusive schools. The results of this study are that educators who support the concept of child-friendly schools in inclusive schools will demonstrate their commitment to inclusivity. in school practices and policies. A flexible teaching approach will be the hallmark of educators in child-friendly schools in inclusive schools. Also, educators at child-friendly schools in inclusive schools will utilize supporting technology to support inclusive learning.